2017
DOI: 10.1371/journal.pone.0181600
|View full text |Cite
|
Sign up to set email alerts
|

Role of HTRA1 in bone formation and regeneration: In vitro and in vivo evaluation

Abstract: The role of mammalian high temperature requirement protease A1 (HTRA1) in somatic stem cell differentiation and mineralized matrix formation remains controversial, having been demonstrated to impart either anti- or pro-osteogenic effects, depending on the in vitro cell model used. The aim of this study was therefore to further evaluate the role of HTRA1 in regulating the differentiation potential and lineage commitment of murine mesenchymal stem cells in vitro, and to assess its influence on bone structure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…These observations imply that HtrA1 plays a role in the pathogenesis of various diseases by modulating proteins in the ECM or cell surface. Although controversial, HtrA1 has been proposed as a key molecule in osteogenesis and chondrogenesis [ 14 , 17 , 18 ]. HtrA1 expression is induced during hypertrophic change in chondrocytes, with the up-regulation of the type X collagen marker in keloid lesions [ 9 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…These observations imply that HtrA1 plays a role in the pathogenesis of various diseases by modulating proteins in the ECM or cell surface. Although controversial, HtrA1 has been proposed as a key molecule in osteogenesis and chondrogenesis [ 14 , 17 , 18 ]. HtrA1 expression is induced during hypertrophic change in chondrocytes, with the up-regulation of the type X collagen marker in keloid lesions [ 9 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…HtrA3 may complement the function of HtrA1 in humans. The deletion of HtrA1 in mice has been shown to influence the aged bone phenotype; bone volume and repair from fractures were not affected in 16-week-old HtrA1-deficient mice, but bone volume increased significantly in 52-week-old HtrA1-deficient mice 31 . HtrA1 deficiency may have suppressed osteoclastogenesis due to the reduced RANKL/OPG ratio in old mice.…”
Section: Discussionmentioning
confidence: 97%
“…10). In this regard, it appears that there is redundancy in proteolytic activity between HtrA3 and HtrA1 31 . We confirmed that HtrA3 is also able to degrade OPG (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some inconsistent results regarding the effects of HTRA1 on bone formation may be due to complex interactions between HTRA1 and TGF‐β family proteins in different cells and dosages of HTRA1 used in each experimental design. Further understanding the role of HTRA1 in bone formation and bone resorption might help to develop HTRA1 a therapeutic target in bone metabolic diseases such as osteoporosis …”
Section: The Potential Role Of Htra1 In Bone Formation and Resorptionmentioning
confidence: 99%